3D Ordering at the Liquid–Solid Polar Interface of Nanowires. Issue 38 (6th August 2020) - Zamani, Mahdi; Imbalzano, Giulio; Tappy, Nicolas; Alexander, Duncan T. L.; Martí‐Sánchez, Sara; Ghisalberti, Lea; Ramasse, Quentin M.; Friedl, Martin; Tütüncüoglu, Gözde; Francaviglia, Luca; Bienvenue, Sebastien; Hébert, Cécile; et al.
Abstract: The nature of the liquid–solid interface determines the characteristics of a variety of physical phenomena, including catalysis, electrochemistry, lubrication, and crystal growth. Most of the established models for crystal growth are based on macroscopic thermodynamics, neglecting the atomistic nature of the liquid–solid interface. Here, experimental observations and molecular dynamics simulations are employed to identify the 3D nature of an atomic‐scale ordering of liquid Ga in contact with solid GaAs in a nanowire growth configuration. An interplay between the liquid ordering and the formation of a new bilayer is revealed, which, contrary to the established theories, suggests that the preference for a certain polarity and polytypism is influenced by the atomic structure of the interface. The conclusions of this work open new avenues for the understanding of crystal growth, as well as other processes and systems involving a liquid–solid interface. Abstract : Experimental observations and molecular dynamics simulations highlight the 3D nature of atomic‐scale ordering of liquid Ga in contact with solid GaAs in a nanowire growth configuration, elucidating the role played by the liquid ordering in controlling the growth.